Literature Review: Efektivitas Program Tablet Tambah Darah dan Asupan Protein dalam Pencegahan Anemia pada Remaja Putri - Harahap, Afifa Naura; Purba, Rumida; Nainggolan, Efendi S (Media Gizi Ilmiah Indonesia, 2023)
Anemia is a condition where the number and size of red blood cells or hemoglobin concentration are below established standards. Anemia in men has a hemoglobin level of less than 13.5 gr/100 ml and in women as hemoglobin less than 12.0 gr/100 ml. The aim to determine effectiveness of the blood supplement tablet program and protein intake in preventing anemia in female adolescents. This study uses the literature review method. Database searches were carried out on Google Scholar, Garuda Portal, DOAJ and PubMed. There were 420 articles found, articles were selected according to title, free access, full text, PICOS, female adolescent population, intervention given the intervention, comparison had no comparison for quasy experiments, study design was experimental design or quasy experiment, and articles published in 2015 -2020 as well as an appraisal checklist and 13 articles were obtained. The results of the study showed that of the 13 articles reviewed, there were 8 articles discussing the effectiveness of the blood supplement, and 5 articles reporting protein intake. The conclusions of 8 articles regarding the effectiveness of the blood supplement tablet program, and the program to increase Hb levels to the highest Hb 1.55 g/dl was supplementation of 200 mg Fe tablets/day with the rule of drinking 1x1 a day for 30 days. Five articles regarding protein intake, and raising the highest Hb level to 2.17 g/dl, namely the administration of 100 g rainbow crowfish cookies containing 17.9 g protein, 1 time/day for 30 days.